2023
DOI: 10.3389/fpls.2023.1294195
|View full text |Cite
|
Sign up to set email alerts
|

Testing effects of vapor pressure deficit on fruit growth: a comparative approach using peach, mango, olive, orange, and loquat

Alessandro Carella,
Roberto Massenti,
Riccardo Lo Bianco

Abstract: Determining the influence of vapor pressure deficit (VPD) on fruit growth is a key issue under a changing climate scenario. Using a comparative approach across different fruit tree species may provide solid indications of common or contrasting plant responses to environmental factors. Knowing fruit growth responses to VPD may also be useful to optimize horticultural management practices under specific atmospheric conditions. Climate data to calculate VPD and fruit relative growth rates (RGR) by fruit gauges we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Carella et al used fruit gauges to test the effect of the vapor pressure deficit (VPD) on the fruit relative growth rate (RGR), by comparing data of peach, mango, loquat (Eriobotrya japonica Lindl. ), olive, and orange [209].…”
Section: Fruit-mounted Sensors Fruit Gaugesmentioning
confidence: 98%
“…Carella et al used fruit gauges to test the effect of the vapor pressure deficit (VPD) on the fruit relative growth rate (RGR), by comparing data of peach, mango, loquat (Eriobotrya japonica Lindl. ), olive, and orange [209].…”
Section: Fruit-mounted Sensors Fruit Gaugesmentioning
confidence: 98%
“…Studies have shown that fruit growth was influenced by plant transpiration [13,14]. Because all sap flow passing through the leaf stalks would evaporate into the air through the leaves, sap flow sensors installed on the leaf stalks could be used to study transpiration [15][16][17][18].…”
Section: Sap Flow Rate (Mg/min) Of Fruit Stalk and Leaf Stalkmentioning
confidence: 99%